ANALISIS EMISI KARBON PROYEK PSDABM DI KAWASAN HUTAN KABUPATEN LOMBOK TIMUR - LALU MUH. KABUL; AGUS MARJAN SAPUTRA (Universitas Mahasaraswati Mataram, 2020)
This study analyzed initial condition of PSDABM project carbon emission. The study method used was mixed method, quantitative and qualitative. The result of study showed that carbon emission in KPHL Rinjani Timur is 0.93 Mt C in 1990-2012 or average 1.10% per year. According to carbon stock, lingkar TNGR has 80-100 ton C/Ha (moderate), for Hutan Gong (KPHL Rinjani Timur), 110.48 ton C/Ha (good) and for Kebun Raya Lemor (KPHL Rinjani Timur), 107.55 ton C/Ha (good). Meanwhile, only HKm Sambelia has low carbon stock with 7.32 ton C/Ha. Social forestry will bean appropriate strategy to increase the forest carbon stock